2016
DOI: 10.3109/03009734.2015.1134733
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between initial cleft size and dental anomalies in unilateral cleft lip and palate patients after alveolar bone grafting

Abstract: ObjectiveTo determine in individuals with unilateral cleft lip and palate the correlation between initial cleft size and dental anomalies, and the outcome of alveolar bone grafting.MethodsA total of 67 consecutive patients with non-syndromic unilateral complete cleft lip and palate (UCLP) were included from the cleft lip and palate-craniofacial center, Uppsala University Hospital, Sweden. All patients were operated by the same surgeon and treated according to the Uppsala protocol entailing: lip plasty at 3 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…The width of the cleft. However, Jabbari et al found the width of cleft has no effect either on the success or failure of the SABG [22,39] 6. The classification of malocclusion [39,40] 7.…”
Section: The Height Of the Intermediary Formed Septa [37]mentioning
confidence: 99%
See 3 more Smart Citations
“…The width of the cleft. However, Jabbari et al found the width of cleft has no effect either on the success or failure of the SABG [22,39] 6. The classification of malocclusion [39,40] 7.…”
Section: The Height Of the Intermediary Formed Septa [37]mentioning
confidence: 99%
“…However, Jabbari et al found the width of cleft has no effect either on the success or failure of the SABG [22,39] 6. The classification of malocclusion [39,40] 7. The canine position relative to the gap in its pre-eruptive phase [39,41].…”
Section: The Height Of the Intermediary Formed Septa [37]mentioning
confidence: 99%
See 2 more Smart Citations
“…The cleft size was measured on dental casts at the time point of primary lip plasty. It was found that the width of the cleft had a positive correlation with prevalence of enamel hypoplasia (Jabbari, Reiser et al 2016). Findings in another study mentioned earlier by Ruiz et al support this notion that the cleft itself may influence the prevalence of enamel defects.…”
Section: Enamel Hypoplasiamentioning
confidence: 70%